Outer Space Militarization and Normative Gaps in International Space Law: A Comparative Legal Analysis - Isnurwanto, Iwan; Birahayu, Dita; Ehirim, Ugochukwu Godspower (Universitas Negeri Gorontalo, 2026)
Disagreements between spacefaring states' strategic activities and the normative goals of international space law have persisted despite space's growing militarization. At the heart of this conflict is the fact that different legal understandings of the term